Konsolidasi demokrasi melalui pengembangan karakter kewarganegaraan - Cholisin Cholisin (Universitas Negeri Yogyakarta, 2004)
The transition from authoritarianism to democracy is prolonged and complex process. From the national united background, he processes of transition flows through three phase (1) preliminary step, i.e. struggling to replace regime; (2) decision step, i.e. building democratic institution: and (3) consolidation step, i.e. the process in which institution and democratic practice initialized in political culture. Civic disposition, both private and public, as an element of civic education, built very determined by two other components, i.e. civic knowledge and civic skill, is a factor which a develop democracy consolidation. Civic disposition is a minor of civic culture, which is as democratic political culture